Agro-Industrial Wastes Revalorization as Feedstock: Production of Lignin-Modifying Enzymes Extracts by Solid-State Fermentation Using White Rot Fungi - Contreras-Villacura, E; Gutierrez-Silva, A; Sepulveda-Cuevas, L; Cerro-Munoz, D; Flores-Rios, R (Taylor and Francis Ltd., 2023)
The purpose of the study was to evaluate the production of lignin-modifying enzyme extracts and delignified biomass from agro-industrial wastes using white rot fungi (Inonotus sp. Sp2, Stereum hirsutum Ru-104, Bjerkandera sp. BOS55, Pleurotus eryngii IJFM 169 and Phanerochaete chrysosporium BKM-F-1767). These were screened based on their adaptability and colonization ability on different substrates, as well as by the Laccase, Manganese peroxidase, and Lignin peroxidase enzymatic production. Native strains (Inonotus sp. Sp2 and S. hirsutum Ru-104) showed the highest growth kinetics under the solid-substrate fermentation conditions and the growth rate parameters of the kinetic logistic model for the different substrates were between 0.39–0.81 (1/d) and 0.42–0.83 (1/d), respectively; the determination coefficients were ≥0.99. Inonotus sp. Sp2 was subsequently cultured in static flasks to produce crude enzyme extracts, obtaining manganese peroxidase activity levels of 18.5 and 31.3 (U/g) when growing in corn cob husk and spent tea leaves, respectively. Besides, it was to establish that the best conditions for lignin-modifying enzymes production using corn cob husk are 70% of initial moisture and 2.12 mm of particle size; reaching after 30 incubation days a manganese peroxidase activity of 21 ± 6 (U/g) under these conditions; enzyme that showed a suitable thermostability. © 2022 Taylor & Francis Group, LLC.